1969
DOI: 10.1113/jphysiol.1969.sp008744
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular responses in apnoeic asphyxia: role of arterial chemoreceptors and the modification of their effects by a pulmonary vagal inflation reflex

Abstract: SUMMARY1. In the spontaneously breathing anaesthetized dog, the systemic circulation was perfused at constant blood flow; there was no pulmonary blood flow and the systemic arterial blood Po. and PCO, were controlled independently by an extracorporeal isolated pump-perfused donor lung preparation. The carotid and aortic bodies were separately perfused at constant pressure with blood of the same composition as perfused the systemic circulation.2. Apnoeic asphyxia, produced by stopping the recipient animal's lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

1970
1970
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(24 citation statements)
references
References 30 publications
3
21
0
Order By: Relevance
“…The present data provide evidence that sex modifies the vascular response to apnea-induced hypoxemia in healthy humans and might also stimulate future work in patients with OSA. Both obstructive apnea during sleep and MVEEA during wakefulness activate the sympathetic nervous system (19,26,32,40,60). Specifically, Greaney et al (18) observed a 51% increase in MSNA in response to MVEEA, Hardy et al (19) noted a 94% increase in MSNA, and Leuenberger et al (40) documented a ϳ200% increase in MSNA in response to this same stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…The present data provide evidence that sex modifies the vascular response to apnea-induced hypoxemia in healthy humans and might also stimulate future work in patients with OSA. Both obstructive apnea during sleep and MVEEA during wakefulness activate the sympathetic nervous system (19,26,32,40,60). Specifically, Greaney et al (18) observed a 51% increase in MSNA in response to MVEEA, Hardy et al (19) noted a 94% increase in MSNA, and Leuenberger et al (40) documented a ϳ200% increase in MSNA in response to this same stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous measurement of arterial oxygen tension during apnoea was not available to us and we are therefore not able definitively to ascribe these cardiovascular changes to hypoxia. Similar cardiovascular responses to hypoxia are, however, well established in animals and it has been shown that these responses are mediated primarily by the peripheral chemoreceptors in the dog (Daly and Scott, 1962;Cross et al, 1963;Angell James and Daly, 1969), cat (Downing and Siegel, 1963), rabbit (Chalmers et al, 1967), and fetal lamb (Dawes et al, 1969) during the last third of gestation. The shortest time interval between onset of apnoea and onset of bradycardia, and between the end of apnoea and cardiac acceleration were both about 2 seconds.…”
Section: * -E~~~~~~~~~~~~~~~mentioning
confidence: 90%
“…When breathing restarts the bradycardia would be expected to be eliminated either by lung inflation over-riding the primary effect of arterial hypoxia (Daly and Scott, 1962; Angell James and Daly, 1969) or by relief of the hypoxia itself. Cardiac acceleration was sometimes delayed up to 16 seconds after breathing restarted.…”
Section: * -E~~~~~~~~~~~~~~~mentioning
confidence: 99%
“…Interruption of the excitatory process could occur by a hyperpolarizing transmitter action at the motor neurone cell surface itself or by other mechanisms operating upstream such as pre-synaptic inhibition or interference with transmission between relay interneurones. The localization of an inhibitory site in the region of the inspiratory centre suggests that the central connexions utilized were those which participate in the pulmonaryvagal inflation reflex described by Angell James & Daly (1969).…”
Section: Discussionmentioning
confidence: 99%